Jacques Cartier : navigating the St. Lawrence River - Greene, Meg (New York : Rosen Pub., 2003)
Describes the life and travels of Jacques Cartier, the sixteenth-century French navigator who made three voyages to what is today known as Canada, in search of a northwest passage to China.
The making of an explorer -- A royal commission -- The new world -- An amazing discovery -- The deadly winter -- The Roberval expedition -- A forgotten discovery? -- The boldest spirit.
10 years and up
Keywords: Cartier, Jacques -- 1491-1557; Cartier, Jacques -- 1491-1557.; Explorers -- America -- Biography -- Juvenile literature; Explorers -- France -- Biography -- Juvenile literature; Explorers; Canada -- Discovery and exploration; Saint Lawrence River -- Discovery and exploration; Canada -- History -- To 1763 (New France); Canada -- Discovery and exploration; Canada -- History -- To 1763 (New France)